Risk assessment on landsacpe development using remote sensing and geographic information system (GIS): Assessment of the impact of agricultural development on soil loss and degradation of ecological service values and goods - Hashim, Mazlan; Okuda, Toshinori (National Institute for Environmental Studies, Japan, 2005)
Amongst the impacts of converting forest to agricultural activities is the degradation of ecology service values and goods (ESVG). Impacts on ESVG can be devastating in environmental, biological, and socio-economics manners. This paper highlights the study undertaken on the impacts of agricultural development in 0.8x106ha of forest dominated landscape in Pasoh Forest Region (PFR), Malaysia, within period of 8 years from 1995 to 2003. Four folds of impacts on agricultural development examined and analysed are: (i) relationship of total soil loss and changes in land use pattern, (ii) relationship of forest water yield and changes in the landscape patterns, (iii) mapping trends of ESVG for PFR in 1995 and 2003, and (iv) risk assessment of ESVG based on simulation of converting 339x103ha of primary forest into mass-scale oil palm plantation. Results of this study indicated that although only minor changes of about 1464ha (~0.2% of PFR) of primary forest was converted to agricultural activities, it have significantly increased the total soil loss from 59x106 to 69x106 t/ha/yr. The mean rate of soil loss within PFR is 0.8x106 t/yr, and if translated into ESVG term, costing US$4.8 x106/yr. However, majority of the soil loss within all land use classes are within range of very low - low risk categories (<10 t/ha/yr). Estimated cost of ESVG for PFR was US$179x106 in 1995, declined to US$114x106 in 2003 due to 0.2% reduction of forested land. Converting 339x103 ha primary forest into mass plantation cost less than original forest within period of 20 years examined; the 20th year of conversion, the ESVG of plantation and to-remain as forest cost US$963x106 and US$575x106, respectively. This difference, however, is only marginal when full 17 attributes of ESVG were considered